1, 2:5, 6‐Di‐O‐Cyclohexylidene‐d‐Mannitol and Its Bis(Trimethylsilyl) Ether in the Dithiophosphorylation Reactions. Issue 2 (15th January 2016) - Nizamov, Ilyas S.; Nikitin, Yevgeniy N.; Belov, Timur G.; Nizamov, Ilnar D.; Voloshina, Alexandra D.; Cherkasov, Rafael A.
ABSTRACT: The reaction of 2, 4‐diaryl 1, 3, 2, 4‐dithiadiphosphetane‐2, 4‐disulfide with diketonide ofd ‐mannitol has been found to give optically active bisaryldithiophosphonic acids transformed into the corresponding diammonium salts by the treatment of n ‐hexadecylamine. O, O ‐Bis(trimethylsilyl) ether ofd ‐mannitol ketonide reacts with 2, 4‐diaryl 1, 3, 2, 4‐dithiadiphosphetane‐2, 4‐disulfide to form chiral S, S ‐disilylbisaryldithiophosphonate. Diammonium bisaryldithiophosphonate possesses antibacterial activity against Staphylococcus aureus ATCC 6538‐P.